Assessing the representation of South American monsoon features in Brazil and U.K. climate model simulations. Issue 1 (2nd December 2021) - Coelho, Caio A. S.; de Souza, Dayana C.; Kubota, Paulo Y.; Cavalcanti, Iracema F. A.; Baker, Jessica C. A.; Figueroa, Silvio N.; Firpo, Mári A. F.; Guimarães, Bruno S.; Costa, Simone M. S.; Gonçalves, Layrson J. M.; Bonatti, José P.; Sampaio, Gilvan; et al.
Abstract: This paper assesses how well the CPTEC/INPE Brazilian Global Atmospheric Model (BAM‐1.2) and the atmospheric component of the UK Met Office Hadley Centre Global Environment Model (HadGEM3‐GC3.1) represent the main South American monsoon features. Climatological (1981–2010) ensemble means of Atmospheric Model Intercomparison Project (AMIP)‐type climate simulations are evaluated. The assessment evaluated the models' ability to represent the South America austral summer and winter precipitation contrast and associated circulation, key South American monsoon system elements, the association between south‐east Brazil and South America precipitation, and climatological (1997/1998 to 2013/2014) distributions of rainy season onset and demise dates over south‐east Brazil (15°S–25°S, 40°W–50°W) and the core monsoon region (10°S–20°S, 45°W–55°W). Despite some identified deficiencies, both models depict the monsoon region and represent the main features, including (1) the north‐west–south‐east precipitation band and associated ascending motion over central South America; (2) the upper‐level Bolivian High and the north‐east South America trough during the summer; (3) the lower‐level South Atlantic and Pacific subtropical anti‐cyclones and (4) the low‐level jet east of the Andes. Both models represent upper‐level divergence and lower‐level convergence over the core monsoon region, and upper‐level convergence and lower‐level divergence over the Pacific and Atlantic anti‐cyclones associated with the regional Walker circulation during the pre‐monsoon (spring) and peak monsoon (summer) seasons. Convection over South America is weaker in BAM‐1.2 than observed, consistent with continental precipitation deficit. The models reproduce the dipole‐like precipitation pattern between south‐east Brazil and south‐eastern South America during the austral summer but overestimate these patterns spatial extent over the South Atlantic. Both models simulate the main observed climatological features of rainy season onset and demise dates for the two above defined investigated regions. HadGEM3 overestimates onset dates interannual variability. These results can contribute towards understanding climate and land‐use change implications for environmental sustainability and for recommending climate adaptation strategies. Abstract : Graphical Abstract : This paper assessed how well the CPTEC/INPE Brazilian Global Atmospheric Model (BAM‐1.2) and the UK Met Office Hadley Centre Global Environment Model (HadGEM3‐GC3.1) represented the main South American monsoon features. Despite the identified model deficiencies, both models adequately represented the main monsoon features. The models consistently represented upper‐level divergence and lower‐level convergence over the core monsoon region, and the upper‐level convergence and the lower‐level divergence over the subtropical anti‐cyclones in the Pacific and Atlantic associated with the regional Walker circulation. Figure Austral summer (DJF) climatological (1981–2010) seasonal mean outgoing longwave radiation (OLR, shaded, W·m −2 ) overlaid with velocity potential (isolines, 10 6 m 2 ·s −1 ) and divergent wind (arrows, m·s −1 ) at 200 hPa (first row) computed using observations (first column, ERA5) and the ensemble means of the two investigated climate models [second column (BAM‐1.2) and third column (HadGEM3)]. Corresponding climatological (1981–2010) seasonal mean precipitable water (PWAT, shaded, Kg·m −2 ) overlaid with velocity potential (isolines, 10 6 m 2 ·s −1 ) and divergent wind (arrows) at 850 hPa (second row). Corresponding vertical climatological (1981–2010) seasonal meridional mean (between 10°S and 30°S) negated vertical velocity (minus omega in Pa·s −1 × 10 3 displayed as arrows) and specific humidity (shaded, g·Kg −1 ) profiles from 1000 to 10 hPa.